Activity Approach and Practice-oriented Primary Teacher Training, Experience of the Siberian Federal University - Smolyaninova O.G.; Korshunova V.V. (Психологическая наука и образование (2007. Online), 2015)
Current issue was done under the Federal Target Education Development Program from 2011 to 2015, with the aim of networking development in vocational secondary education for teacher training based on new modules of applied bachelor programs focused on strengthening the practical orientation of future teacher training. This is considered as a basis of improvement of the federal higher educational standards, the development of new basic exemplary educational programs and finding new ways of educational outcomes assess according to the teacher professional standard. The authors believe that the successful activity in this area will improve the quality of primary school teachers training and will reduce the shortage of personnel in primary education and in secondary vocational education in Russia and Krasnoyarsk Territory in particular.